Testing of materials perspective for nuclear fusion reactors with inertial plasma confinement by Plasma Focus and laser devices. (December 2019) - Gribkov, V A; Demina, E V; Kazilin, E E; Latyshev, S V; Maslyaev, S A; Pimenov, V N; Paduch, M; Zielinska, E; Laas, T
Abstract: A survey of consequences on recent testing of materials perspective for the fist-wall components of nuclear fusion chambers with inertial plasma confinement is presented. The main instruments in these irradiation experiments were Dense Plasm Foci facilities of different energy levels and Nd-glass lasers. Results of investigations of physical processes of interaction of powerful plasma jets, streams of fast ions and laser beams with the targets under tests are discussed. Subsequent analytical researches of various characteristics of damageability of dissimilar samples – both surface and bulk of them – are debated.